Kontrol Elektronik Mesin Penetas Telur Hybrid Matahari Berbasis Arduino - Siswoko Siswoko; Edi Sulistio Budi; Achmad Komarudin (Integrated Lab Journal, 2020)
This paper presents the electronic control of a solar hybrid egg incubator using Arduino. In the process of hatching eggs, there are 2 methods, namely naturally incubated by the parent itself and artificially by using an egg incubator. In general, egg incubators utilize electrical energy, where we know that electrical energy from fossils is expected to run out in 2020. In this solar hybrid egg incubator, it is able to minimize the use of electricity and is environmentally friendly which uses 2 energies, namely, sunlight as a source of heat in the process of hatching eggs and electrical energy with a heater as the actuator to back up when the heat absorbed does not meet the needs. In the process of hatching eggs, heat energy is required in the form of a temperature of 29 to 34 degrees Celsius. In the process of absorbing sunlight, heat storage accumulators are used directly. By using a heat storage accumulator and utilizing this heat energy directly, it can optimize energy from the sun by 80%, in contrast to solar panels that absorb solar energy and convert solar energy to electrical energy in a maximum of 20%.